2019
DOI: 10.15835/nbha47411613
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Reducing Lead and Cadmium Absorption by Alfalfa (Medicago scutellata L.) in a Contaminated Soil Using Nano-Activated Carbon and Natural Based Nano-Zeolite

Abstract: The first risk posed by heavy metal pollution in an ecosystem is metal accumulation in the biomass of growing plants, which has harmful effects on human health. Natural-based nanoparticles are efficient in remediating environmental pollutants because they have a high surface/volume ratio, high chemical activity and produce no harmful side-products. The present study investigates the capacity of natural-based nano-porous adsorbents for reducing the availability of heavy metals to annual alfalfa (Medicago scutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, both positive and negative effects of NPs are observed in plants (Zhu et al, 2019). In recent years, NPs have received considerable attention due to their applications in technology and sciences (Salehi et al, 2018;Hasanabadi et al, 2019;Vicas et al, 2019). So, before its widespread employment and applications in the life, its probable influences on living beings and environment should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both positive and negative effects of NPs are observed in plants (Zhu et al, 2019). In recent years, NPs have received considerable attention due to their applications in technology and sciences (Salehi et al, 2018;Hasanabadi et al, 2019;Vicas et al, 2019). So, before its widespread employment and applications in the life, its probable influences on living beings and environment should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Hasanabi et al [116] analysed the effects of natural nano-zeolite, modified nano-zeolite, and nanoporous activated carbon on Pb and Cd concentration in polluted soil. The results demonstrated that the use of modified nano-zeolite reduced the shoot Pb and Cd content by 33.2% and 46.7%, respectively.…”
Section: Natural Zeolites and Soil Pollutionmentioning
confidence: 99%